3D Modeling Parallel Coupled-Line Bandpass Filter Based on Coplanar Waveguide MMIC Multilayer Technology - Rizqi Eka Putri; Emerson Pascawira Sinulingga; Suherman Suherman (TELKA - Jurnal Telekomunikasi, Elektronika, Komputasi dan Kontrol, 2019)
Electromagnetic modeling technique on monolithic microwave integrated circuit (MMIC) coplanar waveguide (CPW) multilayer have been developed to accurately model the Parallel Coupled-Line Bandpass Filter. The 3D modeling technique shows the simulation results that are optimum. Several simulation steps have been demonstrated and compared on the design of Parallel Coupled-Line Bandpass Filters. Based on the 3D modeling, S11-Return Loss and S21-Insertion Loss of -22.6 dB and and 2.94 dB are obtained respectively. In addition, it is shown the best frequency response from the design of the Parallel Coupled-Line Bandpass Filter.